DISTRIBUTED WAREHOUSING FOR VIBRATIONAL SIGNALS ANALYSIS SYSTEM - V. E. Bazarevsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Article covers the methods of vibration signals long implementations analysis as well as complex analysis of large amounts of signal data. Several architectural pattern applications of signal and analytical data warehouses for decision support system that evaluates the vibration characteristics of the objects are proposed. The ways of extending and embedding third-party functionality in MS SQL Server engine are recommended.